Proteomic analysis of dog tears for potential cancer markers - Campos, Carla de Freitas [UNESP]; Cole, Nerida; Van Dyk, Derek; Walsh, Bradley J.; Diakos, Penelope; Almeida, Denise [UNESP]; Torrecilhas, Adriana [UNESP]; Laus, Jose Luiz [UNESP]; Willcox, Mark D. P. (Elsevier B.V., 2008)
The first reference map of the proteome of pooled normal dog tears was created using 2-dimensional polyacrylamide gel electrophoresis and the identity of a number of the major species determined using matrix-assisted laser desorption time of flight mass spectrometry (MALDI-TOF) and peptide mass fingerprint matching on protein sequence databases. In order to understand the changes in protein expression in the tear film of dogs with cancer, tears from such animals were similarly examined. A number of differences were found between the tears of healthy dogs and the dogs with cancer. Differences were found in levels of actin and albumin and in an unidentified protein which may be analogous to human lacryglobulin. These findings suggest that it may be possible to develop tear film analysis to provide a simple non-invasive test for the diagnosis and/or management of canine cancers. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 2-dimensional electrophoresis; Dog; tears; neoplasm